(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
This article is devoted to the importance of developing reading comprehension skills in foreign language teaching in journalism. In learning a foreign language, the main focus is on the formation of students’ reading comprehension skills. The article analyzes the specific features of reading comprehension in journalism, the methodical methods used to develop this skill, as well as the role of modern teaching technologies. Emphasis is placed on the importance of reading comprehension, particularly in journalism, in gathering information quickly and accurately, analyzing it, and covering universal topics.